PENGARUH PEMBERIAN KOMPOS ECENG GONDOK DAN PENGATURAN JARAK TANAM TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KEDELAI (Glycine max L. Merrill) - Ronny Ardiansyah; Husna Yetti; Sri Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The objective of this study was todetermine the effect, interaction and get the dose of water hyacinth compost and appropriate plant spacing to the growth and yield of soybean. The study was conducted in the experimental station of Agriculture Faculty of Riau University by using a randomized completely block design with 2 factors and3 replications. The first factor was water hyacinth compost consisted of 5 levels namely: 0 t.ha-1, 5 t.ha-1, 10 t.ha-1, 15 t.ha-1and20 t.ha-1water hyacinth compost. Meanwhile the second factor was plant spacing which consisted of 2 levels namely: (40 x 15) cm and (40 x 20) cm. The result of this study indicated that water hyacinth composting give effected on plant height, number of branches, number of pods per plant, number of filled pods per plant, seed weight per plant, seed weight per plot, seed weight per m2andweight of 100 seeds, while plant spacing give effected on seed weight per plot andseed weight per m2. Combination of water hyacinth composting 15 t.ha-1 and plant spacing (40 x 15) cm give the highest results of plant height, seed weight per plot and seed weight per m2 meanwhile combination of water hyacinth composting15 t.ha-1 and plant spacing (40 x 20) cm give the highest results of number of branches, number of pods per plant, number of filled pods per plant, seed weight per plantandweight of100 seeds. Keywords : Water hyacinth compost, plant spacing, yield components